Using Vibration to Guide Exploration of Haptic Graphics - Lowe, Richard (Universite Pierre-Mendes-France, 2012)
Haptic guidance offers a non-visual way of cueing appropriate direction of learner attention in complex animated displays. This methodological paper describes a haptic panel capable of providing vibration in specific locations to guide search or signal target elements. The panel allows the effectiveness of haptic arrays with and without vibration to be compared. A measure of search efficiency in terms of panel area explored was developed using video records of participants’ hand movements. Construction and operation of the panel are described together with the approach used to characterize the effects of vibration on tactile search.